Implementation of the Icelandic Prevention Model: a critical discussion of its worldwide transferability. (4th July 2021) - Koning, Ina M.; De Kock, C.; van der Kreeft, P.; Percy, Andrew; Sanchez, Zila M.; Burkhart, G.
Abstract: Environmental drug prevention interventions are gaining momentum alongside and in concert with 'classical' prevention practices such as school, family and community interventions. The Icelandic Prevention Model (IPM) is particularly gaining attention because of its innovative environmental approach and because of its supposed impact on lowering (the onset of) substance use among youth during the past two decades in Iceland. Although this model is rooted in well accepted prevention principles and has been prominent in public discussions and the media across the world, much remains unknown about the active ingredients, the core elements and their contribution to lowering (the onset of) substance use among youth. In this discussion paper we highlight the model's strengths (bottom-up approach, local assessment and dissemination, multi-component, targeting risk and protective factors, supervised leisure activities, curfew hours) and raise some critical concerns (transferability, external and internal validity) that should be considered and dealt with before implementing, adapting and evaluating the model in other contexts.